Generation Z’s Perception of the Relevance of Pancasila in the Digital Era - Dhea Isfani Putri AP Lubis; Ela Sari Br Ginting; Nilam Artika Sari; Nurul Khairunisa; Rosela Hartati Harefa; Anugrah Setiawan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to explain how Generation Z views the importance of Pancasila as the foundation of the nation in the digital era. The study uses a qualitative method by collecting data through in-depth interviews with five individuals from the Generation Z group. The results show that Generation Z regards Pancasila as a moral guideline and a foundation for social life, although the meanings they understand vary and are not always practiced in the digital world. However, all respondents agree that Pancasila remains relevant as an ethical guide, especially in addressing issues such as fake news, misleading speech, and division on social media. A major challenge faced by Generation Z is the vast amount of digital information and the influence of global culture, which can alter their understanding of national values. The study concludes that to internalize Pancasila, it must be done in a more creative, contextual, and experience-based manner aligned with the digital lives of Generation Z.